PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA ANGGOTA POLRI TINGKAT BINTARA PADA KEPOLISIAN RESOR OGAN KOMERING ULU DI BATURAJA - Putriani, Dyah Ayu (Jurnal Manajemen, 2019)
The formulation of the problem in this research is what the influence of working environment and work discipline on the performance of POLRI member of Bintara level at Ogan Komering Ulu Resort Police in Baturaja. While the purpose of this research is to know how big the influence of work environment and work discipline to the performance of POLRI member of Bintara level at Ogan Komering Ulu Resort Police in Baturaja. The research method used in this research is descriptive method that is a method used to describe or analyze a research result but is not used to make wider conclusion. Multiple linear regression equations are obtained as follows: Y = - 0.645 + 0.482X1 + 0.494X2 The correlation value (R) is 0.806. This value indicates that the relationship between all independent variables ie work environment and work discipline with dependent variable that the member's performance is very strong because approaching value 1. The value of coefficient of determination (R Square) is equal to 0,649 or 64,9%. This value shows that the contribution of all independent variables is work environment and work discipline with dependent variable that is member performance simultaneously is equal to 64,9%. Meanwhile, the remaining 35.1% was contributed by other factors are not examined. Based on t test, the independent variables are work environment and work discipline partially affect the dependent variable that is the performance of POLRI member of Bintara level at Ogan Komering Ulu Resort Police in Baturaja. Result of F test calculation obtained value of Fhitung equal to 34,216 while Ftabel obtained value equal to 2,316. This means Fcount> Ftable then there is influence of work and work discipline on the performance of POLRI member of Bintara level at Ogan Komering Ulu Resort Police in Baturaja. The Fcount value is 34.216. Ftable value is calculated using a significant level of 0.05 and degrees of freedom (df1) of 2 and degrees of freedom (df2) of 37, to obtain a Ftable value of 2.316. With the value of Fhitung greater than the value of Ftable (34.216> 3.251) then the conclusion refused Ho and accept Ha. Thus simultaneously (together) the independent variables ie work environment (X1) and work discipline (X2) have a significant effect on the performance of member (Y) POLRI Bintara level at Ogan Komering Ulu Resort Police in Baturaja.